1979
DOI: 10.1002/j.1556-6978.1979.tb00902.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Client Reluctance and Counseling Effectiveness

Abstract: The effect of client reluctance, resistance to professional assistance, has received little attention in the research on counseling effectiveness. In a short‐term college counseling situation, it was found that intake measures of client‐reluctance were: (a) negatively correlated with client‐perceived satisfaction and improvement, (b) negatively related to degree of congruence between perceived problem and perceived emphasis of the agency, and (c) positively correlated with premature termination in counseling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…&Wilder, 1979).If the counselor is open, empathic, and clear in explaining his or her role in a genuine and respectful way, we have found that clients often reciprocate by being more open and forthright. This openness can help both the client and counselor to determine whether or not the service to which the client has been mandated is appropriate.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…&Wilder, 1979).If the counselor is open, empathic, and clear in explaining his or her role in a genuine and respectful way, we have found that clients often reciprocate by being more open and forthright. This openness can help both the client and counselor to determine whether or not the service to which the client has been mandated is appropriate.…”
mentioning
confidence: 75%
“…When mandated clients come to counseling they often view the counselor as someone who represents an unjust "system" and, as such, is someone that they need to fight against (Mahrer et al, 1994Paradise & Wilder, 1979. If the counselor is open, empathic, and clear in explaining his or her role in a genuine and respectful way, we have found that clients often reciprocate by being more open and forthright.…”
Section: Walking Alongsidementioning
confidence: 89%
See 3 more Smart Citations